Identifikasi Konteks Ekstralingual Virtual Bahasa Media Sosial sebagai Penunjang Analisis Bahasa sebagai Alat Bukti Hukum - Ali Kusno; M. Bahri Arifin; Widyatmike Gede Mulawarman (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
One of the negative impacts of social media is the rise of language wars. Investigators involve linguists in handling language cases as evidence. In addition to considering lingual elements, linguists also need to pay attention to extralingual elements. One of the extralingual elements can be identified with SPEAKING Dell Hymes. Analysis of social media language needs to pay attention to the virtual extralingual context. This study aims to reveal the virtual extralingual context on social media. The results of this study are useful in the study of forensic linguistics. This research uses the descriptive qualitative method. Research data in language use in social media and language reports as legal evidence. The data sources are social media and police reports which are collected with documentation, listening, and followed by note-taking techniques. Data analysis used the extralingual equivalent method. The results show that each social media has language use characteristics that are influenced by user segments and service features. These characteristics will continue to change following the development of social media features and services. The virtual context of one social media cannot be used to understand the context of another social media. The forensic linguistic analysis makes the results of the analysis scientifically and legally accountable. It is based on the consideration that every result of language analysis as legal evidence made by linguists impacts one's fate.